PENGARUH IMPLEMENTASI PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN FISIKA KELAS XI DI SMA N 5 PADANG - Ifrilla Ramadani (Universitas Negeri Padang, 2014)
low of student critical thinking skill is caused by strategy which used by teacher in learning process was not give enough chance do develop potency of student critical thinking skill, so it is difficult for student to understand physics concept and solving physics problem that needs to analyse. One of applicable strategy could used by teacher to solve this problem is aplly strategy of Problem Based Learning. The goal of this research is to investigate influence of implementation Problem Based Learning to student critical thinking skill in physics learning of XI Grader student in SMAN 5 Padangkind of this research is Quasi Experimental with design of Randomized Control is Only Design's Group . Population in this research is all of XI IPA Grader student in SMAN 5 Padang enrolled in 2013 / 2014. Sample class is determined by Cluster Random Sampling technique. Data collecting ran by written test for cognitive aspect. Data analysis in this research using t-test on real level 0,05 for cognitive aspect. Result of this research shows student critical thinks skill on cognitive aspect. Average value of critical thinks skill in experiment class is 74,9, higher than control class which is 69,09. Hypothesis is tetsted by using t-test and acquired t count = 1,68 and t table = 2,00. It means t computing is in accepting region Ho, therefore Hi is refused. It can be conclude that work hyphothesis “available a significant influence of implementation Problem Based Learning (PBL) to critical thinks skill of student in physics learning in grade XI at SMAN 5 Padang” rejected on real level 0,05